2019
DOI: 10.4025/actasciagron.v42i1.42726
|View full text |Cite
|
Sign up to set email alerts
|

Chemical diversity of accessions of the in vivo germplasm bank of Varronia curassavica (Jacq.)

Abstract: Varronia curassavica (Jacq.) is a shrub and perennial plant native to Brazil that has therapeutic, anti-inflammatory and cicatrizing properties. The objective of this work was to study the chemical diversity of the native populations of this species maintained in the in vivo germplasm bank from Montes Claros, Minas Gerais, Brazil. The essential oils of 10 accessions analyzed in triplicate were obtained by hydrodistillation. Fifty-five compounds were detected, 46 of which were identified by GC-MS analysis. Esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
1
1
0
1
Order By: Relevance
“…), a similar result to those observed by other authors regarding populations of black sage(Nizio et al, 2015;Oliveira et al, 2020;Queiroz et al, 2019). The substances found with greatest frequency were α-humulene (100% frequency) and germacrene D and caryophyllene oxide (both with 94% frequency).Nizio et al (2015) reported that β-caryophyllene was the substance with greatest frequency (100%), while Oliveira et al (2019) and Queiroz et al (2019) reported 100% frequency of αhumulene and β-caryophyllene.…”
supporting
confidence: 91%
“…), a similar result to those observed by other authors regarding populations of black sage(Nizio et al, 2015;Oliveira et al, 2020;Queiroz et al, 2019). The substances found with greatest frequency were α-humulene (100% frequency) and germacrene D and caryophyllene oxide (both with 94% frequency).Nizio et al (2015) reported that β-caryophyllene was the substance with greatest frequency (100%), while Oliveira et al (2019) and Queiroz et al (2019) reported 100% frequency of αhumulene and β-caryophyllene.…”
supporting
confidence: 91%
“…The compositions varied according to the plant age, mainly for less abundant molecules, which were detected in some samples and in others could not be accurately identified. α-Pinene was the most abundant compound of V. curassavica EOs obtained from different regions of Brazil (São Paulo, Rio de Janeiro, Minas Gerais, Bahia, Sergipe and Ceará) [3,27,32,33]. On the other hand, plants of the same species cultivated in Minas Gerais and in the southern region of Bahia (Brazil) showed β-pinene, β-caryophyllene and α-humulene as the major chemical compounds, while α-pinene and caryophyllene were also found [33][34][35].…”
Section: Resultsmentioning
confidence: 99%
“…cadineno, carotol, epóxi-cariofileno e (Z)-y-bisaboleno(Carvalho Júnior et al, 2004;Alves et al, 2019;Queiroz et al 2020). O estudo desenvolvido por Facanali et al (2020) possibilitou a identificação de 135 constituintes do óleo essencial da erva-baleeira com uso da cromatografia gasosa bidimensional.Tabela 2 -Principais compostos químicos presentes no óleo essencial de erva-baleeira (Cordia curassavica (…”
unclassified